Knowledge, Attitude, and Practices of Mothers toward Infant Oral Care Living in Rural Areas of West Godavari District, Andhra Pradesh - Kadali Sushmitha; K. S. Uloopi; Vinay Chandrappa; Penmatsa Chaitanya; Cheeli Spandana; Penmetsa Ahalya (Wolters Kluwer Medknow Publications, 2024)
Context Early childhood caries is the most frequent chronic illness in young children which affects their overall well-being. It is crucial to educate mothers regarding infant oral care since the young children are dependent on their mothers for their basic needs. Aim This study aims to assess the knowledge, attitude, and practices (KAPs) of mothers toward infant oral care living in rural areas. Settings and Design The study was an observational study. Materials and Methods A total of 630 mothers of infants aged 0-2 years living in rural areas of West Godavari District, Andhra Pradesh, were included in the study using multistage sampling. A validated 25-item questionnaire was used to assess the KAPs of mothers regarding infant oral care. After collecting the filed questionnaires, participants were educated on infant oral health. A scoring scale was given for the responses of each question to assess the total scores of each participant. Statistical Analysis Used This was descriptive statistical analysis. Results The mean age of the mothers was 25.06 ± 3.7 years. Among the studied population, about 51.4% of the participants had poor knowledge about infant oral hygiene, 74.1% of the participants had positive attitude toward infant oral care, and 58.5% of the participants had satisfactory levels of infant oral hygiene practices. Conclusion The majority of the infants' mothers had poor knowledge about infant oral care and followed unsatisfactory infant oral hygiene practices. However, they exhibited a positive attitude toward infant oral care.